THE INFLUENCE OF APPLICATION OF GAME BASED PASSING TRAINING MODELS ON SENIOR HIGH SCHOOL STUDENTS PASSING SKILL - Deni Mudian; Moch. Asmawi; Taufik Rihatno (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2020)
Passing skill done by SMP IT Alamy students still too fast and inaccurate, which made difficult for another football player to take the ball. The aim of this study to investigate the effect of application game-based model of passing football training on IT ‘Alamy junior high school. This type of research is an experiment with the design of "The One Group Pretest Posttest Design". The population study was 30 students of IT ‘Alamy Junior High School. Based on the research instrument data shosws the score for validity test is 0.720 and reliability is 0.808. Data analysis using t test with a significance level of 5%. The results shows that there was a significant influence on the application of the passing game model on junior high school IT ‘Alamy students. Thus, a value of t count 6.574> t table 2.09, and a significance value of 0.000 <0.05, and a percentage increase of 37.69%.